The remedies of the soul: therapeutics in Spinoza - Canto, Rafael Estrela (Argumentos - Revista de Filosofia, 2016)
In this paper, we make some reflections about the philosophy as a way of life for Spinoza. We compare it to the philosophy of Epicurus, according to Pierre Hadot interpretation. Therefore, we put in the center of the investigation the concept of remedy, equally present in both philosophers. To this philosophy’s aspect, we give the name of therapeutics.